Diamond Microstructuring by Deep Anisotropic Reactive Ion Etching. Issue 22 (25th July 2018) - Golovanov, Anton V.; Bormashov, Vitaly S.; Luparev, Nikolay V.; Tarelkin, Sergey A.; Troschiev, Sergey Y.; Buga, Sergei G.; Blank, Vladimir D.
Abstract : Fabrication of diamond micro‐patterned structures is a technological challenge due to the outstanding hardness and chemical stability of the material. In this work, the synthetic diamond reactive ion etching (RIE) process is studied. The effects of the gas mixture and bias on the diamond etching rate are investigated. A high etching rate (up to 5 μm h −1 ) is achieved in SF6 based plasmas with the intensive ion sputtering. The features of protective masks on diamond samples fabrication are discussed. Etching selectivities of Al, Ni, Mo, Al2 O3, and AlN as mask materials in SF6 plasma are investigated. The initial size of the mask affects its selectivity. To explain the influence of the initial mask shape on the selectivity, a semi‐empirical model of the diamond‐mask topography transformation under the ion sputtering is proposed. By setting the shape of the masks, it is possible to form diamond structures with any desirable profile using the same etching process: steep walls with 20 μm height, solid immersion lenses with 2–10 μm radii, conic figures, and developed surface. This is a relatively simple and universal method of diamond microstructures fabrication. Abstract : Synthetic diamond reactive ion etching is studied. Etching selectivities of metal and dielectric protective hardmasks are investigated. To explain how the mask shape affects its selectivity, a semi empirical model of diamond‐mask topography transformation under ion sputtering in plasma is proposed. Hardmask faceting effect is applied to design diamond micro‐patterned structures with any desirable profile. This is a relatively simple and universal method of microfabrication.